Research of polyester film for electronic components - Gorišek, Ida (Informacije MIDEM, 1997)
Polyester film is frequently used material in electrical industry. It is used as dielectric and as substrate for different printed circuits. Poor adhesion and low surface energy are the most significant properties of polyester film. Different methods of surface treatment of polyester were used to achieve promotion adhesion for applying polymer resistive paste for potentiometers. Methods of surface treatment with UV and control method were developed.
Keywords: elektronski elementi; lastnosti; poliester; površinska energija; površinska obdelava